Prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from chromosome 16 - Chih-Ping Chen; Tsang-Ming Ko; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Shih-Ting Lai; Chien-Wen Yang; Chen-Wen Pan; Wayseen Wang (Elsevier, 2017)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of a small supernumerary marker chromosome (sSMC) derived from chromosome 16. Case report: A 28-year-old woman underwent amniocentesis at 17 weeks of gestation because of abnormal maternal serum screening for Down syndrome. Amniocentesis revealed a karyotype of 47,XY,+mar[5]/46,XY[9]. Parental karyotypes were normal. Prenatal ultrasound findings were unremarkable. Array comparative genomic hybridization (aCGH) analysis of cultured amniocytes revealed a de novo 16% gene dosage increase of 16q11.2-q22.1. Repeat amniocentesis at 21 weeks of gestation revealed a karyotype of 47,XY,+mar[10]/46,XY[31]. aCGH analysis of uncultured amniocytes revealed a result of arr 16q11.2q22.1 (46,492,626-68,867,969) × 2.20 with a log2 ratio of 0.15 encompassing RPGRIP1L, FTO, SLC6A2, BBS2 and CDH1. Interphase fluorescence in situ hybridization (FISH) analysis on uncultured amniocytes detected partial trisomy 16q in 36/137 (26.3%) of uncultured amniocytes. Polymorphic DNA marker analysis on amniocytes and parental bloods excluded uniparental disomy 16. Premature labor occurred at 25 weeks of gestation, and a 585-g male baby without craniofacial dysmorphism was delivered and survived. At age 1½ years, pediatric follow-ups revealed normal psychomotor development, normal body weight, short stature, congenital hypothyroidism, hearing impairment and hypospadias in the neonate, and the peripheral blood had a karyotype of 46,XY in 40 cultured lymphocytes. Conclusion: aCGH, interphase FISH and polymorphic DNA marker analyses of uncultured amniocytes are useful for confirmation of prenatally detected mosaic sSMCs at amniocentesis.